Electronic, optical, elastic, thermoelectric and thermodynamic properties of the spinel oxides ZnRh2O4 and CdRh2O4 - Bouhemadou, Abdelmadjid; Allali, D.; Boudiaf, Khaouther; Al Qarni, Bandar; Bin-Omran, Saad; Khenata, Rabah; Al-Douri, Yarub (Elsevier, 2019)
Density functional FP-LAPW+lo method calculations were performed to explore the structural, electronic, optical, elastic, thermoelectric and thermodynamic properties of the spinel oxides ZnRh2O4 and CdRh2O4. The exchange-correlation potential were described using the GGA-PBEsol and TB-mBJ functionals. As the first step, the optimized structural parameters, including the lattice parameter and atomic coordinates, were determined. Electronic band structure, atomic-resolved l-projected densities of electronic states and photon energy dependence of the linear optical functions were computed. It is found that both investigated compounds are indirect band gap semiconductors. The band gap results from the splitting of the Rh:4d6 states into occupied Rh:4d−t2g 6 states, which form the valence band maximum (VBM), and the empty states Rh:4d−eg 0, which form the conduction band minimum (CBM), owing to the octahedral substantial crystal-field. The electronic interband transitions responsible of the structures in the optical spectra were specified. Single-crystal and polycrystal elastic moduli, wave sound velocities, Debye temperature, Pugh's indicator and indexes of elastic anisotropy were numerically estimated using total energy versus strain. FP-LAPW+lo band structure in combination with the standard Boltzmann transport theory were employed to calculate the thermoelectric parameters, including Seebeck coefficient, electrical and thermal conductivities and figure of merit. It is found that the title compounds are potential candidates for thermoelectric applications if one can further reduce their thermal conductivities via some techniques. FP-LAPW+lo approach in combination with the quasi-harmonic Debye model was employed to study temperature and pressure dependences of some macroscopic physical parameters. Our obtained results in the present work are discussed in comparison with the available experimental and theoretical data. The calculated results show a good agreement with the available experimental and theoretical results.